OROFACIAL RECONSTRUCTION WITH LOCAL FLAPS AT AFID - Liaqat, Beenish; Ehsan, Afeefa; Baig, Amir Mushtaq; Bukhari, Syed Gulzar Ali (Journal of Ayub Medical College Abbottabad, 2010)
Background: Reconstruction of oral cavity is often a difficult challenge as it involves the restoration of both the cosmetics and preoperative function. Understanding the oral cavity anatomy as well the functional capacities of its various subunits is required to achieve good results. The stage of the disease and extent of resection are the most significant parameters that must be kept in mind before planning for reconstruction. Aim was to evaluate the success rate of various local flaps in oral reconstruction as well as to conclude whether or not the reconstruction method influences postoperative quality of life. Methods: This is a descriptive study carried out at Armed Forces Institute of Dentistry, (AFID) Rawalpindi. Sample size comprises of 24 subjects, 16 males and 8 females, who reported to the diagnostic department of AFID from 15 March 2007 to 15 March 2010. Results: A total of 24 patients with oral squamous cell carcinoma were treated in 3 years, out of them 16 (66.7%) were male and 8 (33.3%) were female. The peak incidence was in the 6th and 7th decade of life (37.5%). The most common site involved was the alveolus 37.5% in the reported cases followed by tongue (25%) and buccal mucosa (25%). In 8 (33.3%) patients local resection was performed, in 4 (16.7%) patients resection along with neck dissection was done. In 12 (50%) patient tumour resection followed by neck dissection and immediate reconstruction was also done out of these 12 patients nasolabial flap reconstruction was done in 6 patient (25%), Karapandzic in 4 (16%) patients, and fan flap in 2 (8%) patients. No complication noticed other than wound dehiscence (2 patients), microstomia and circumoral scarring (1 patient). Mean hospital stay was 7 days. Keywords: Reconstruction, Resection, Local Flaps, Neck Dissection, Tumour, Karapandzic Flap, Nasolabial Flap, Fan Flap, Microstomia, Circumoral Scarring